Toward unidirectional switches: 2-(2-Hydroxyphenyl)pyridine and 2-(2-methoxyphenyl)pyridine derivatives as pH-triggered pivots - Tepper, Christina; Haberhauer, Gebhard (Beilstein Journal of Organic Chemistry, 2012)
The pH-induced switching process of 2-(2-hydroxyphenyl)pyridine and 2-(2-methoxyphenyl)pyridine derivatives was investigated with the help of UV spectroscopy. Quantum chemical calculations at the B3LYP/6-31G* level of theory were performed to show that in the case of 2-(2-methoxyphenyl)-3-methylpyridine and 2-(2-hydroxyphenyl)-3-methylpyridine the rotation during the switching process proceeds unidirectionally at the molecular level. If a 2-(2-methoxyphenyl)pyridine derivative is fixed to a chiral cyclopeptidic scaffold, a unidirectional progress of the rotation is achieved macroscopically.
Keywords: CD spectroscopy; chirality; molecular modeling; molecular switches; unidirectional movements

Molecular Devices and Machines – A Journey into the Nano World - Balzani, V.; Credi, A.; Venturi, M. (Wiley-VCH, 2003)

(untitled) - Kay, E. R.; Leigh, D. A.; Zerbetto, F. (Angew. Chem., Int. Ed., 2007)
Angew. Chem. 2007, 119, 72–196. doi:10.1002/ange.200504313

(untitled) - Shirai, Y.; Morin, J.-F.; Sasaki, T.; Guerrero, J. M.; Tour, J. M. (Chem. Soc. Rev., 2006)

Supramolecular Chirality - Leigh, D. A.; Pérez, E. M. (Dynamic Chirality: Molecular Shuttles and Motors, 2006)

(untitled) - Kinbara, K.; Aida, T. (Chem. Rev., 2005)

(untitled) - Kottas, G. S.; Clarke, L. I.; Horinek, D.; Michl, J. (Chem. Rev., 2005)

(untitled) - Bustamante, C.; Keller, D.; Oster, G. (Acc. Chem. Res., 2001)

(untitled) - Kelly, T. R. (Acc. Chem. Res., 2001)

(untitled) - Feringa, B. L. (Acc. Chem. Res., 2001)

(untitled) - Shinkai, S.; Ikeda, M.; Sugasaki, A.; Takeuchi, M. (Acc. Chem. Res., 2001)

(untitled) - Collin, J.-P.; Dietrich-Buchecker, C.; Gaviña, P.; Jimenez-Molero, M. C.; Sauvage, J. P. (Acc. Chem. Res., 2001)

(untitled) - Schalley, C. A.; Beizai, K.; Vögtle, F. (Acc. Chem. Res., 2001)

(untitled) - Ballardini, R.; Balzani, V.; Credi, A.; Gandolfi, M. D.; Venturi, M. (Acc. Chem. Res., 2001)

(untitled) - Pease, A. R.; Jeppesen, J. O.; Stoddart, J. F.; Luo, Y.; Collier, C. P.; Heath, J. R. (Acc. Chem. Res., 2001)

(untitled) - Zhou, Z.; Cao, C.; Yin, Z.; Liu, Q. (Org. Lett., 2009)

(untitled) - Wang, C.; Zhang, D.; Zhang, G.; Xiang, J.; Zhu, D. (Chem.–Eur. J., 2008)

(untitled) - Chatterjee, M. N.; Kay, E. R.; Leigh, D. A. (J. Am. Chem. Soc., 2006)

Molecular Switches - Feringa, B. L. (Wiley-VCH, 2001)

(untitled) - Pollard, M. M.; Klok, M.; Pijper, D.; Feringa, B. L. (Adv. Funct. Mater., 2007)

(untitled) - Pijper, D.; van Delden, R. A.; Meetsma, A.; Feringa, B. L. (J. Am. Chem. Soc., 2005)

(untitled) - Fletcher, S. P.; Dumur, F.; Pollard, M. M.; Feringa, B. L. (Science, 2005)

(untitled) - Koumura, N.; Zijlstra, R. W. J.; van Delden, R. A.; Harada, N.; Feringa, B. L. (Nature, 1999)

(untitled) - Durola, F.; Lux, J.; Sauvage, J.-P. (Chem.–Eur. J., 2009)

(untitled) - Rescifina, A.; Zagni, C.; Iannazzo, D.; Merino, P. (Curr. Org. Chem., 2009)

(untitled) - Silvi, S.; Venturi, M.; Credi, A. (J. Mater. Chem., 2009)

(untitled) - Silvi, S.; Constable, E. C.; Housecroft, C. E.; Beves, J. E.; Dunphy, E. L.; Tomasulo, M.; Raymo, F. M.; Credi, A. (Chem.–Eur. J., 2009)

(untitled) - Anelli, P. L.; Spencer, N.; Stoddart, J. F. (J. Am. Chem. Soc., 1991)

(untitled) - Lane, A. S.; Leigh, D. A.; Murphy, A. (J. Am. Chem. Soc., 1997)

(untitled) - Haberhauer, G.; Kallweit, C. (Angew. Chem., Int. Ed., 2010)
Angew. Chem. 2010, 122, 2468–2471. doi:10.1002/ange.200906731

(untitled) - Wang, J.; Feringa, B. L. (Science, 2011)

(untitled) - Wang, J.; Hou, L.; Browne, W. R.; Feringa, B. L. (J. Am. Chem. Soc., 2011)

(untitled) - Haberhauer, G. (Angew. Chem., Int. Ed., 2011)
Angew. Chem. 2011, 123, 6539–6543. doi:10.1002/ange.201101501

(untitled) - Tepper, C.; Haberhauer, G. (Chem.–Eur. J., 2011)

(untitled) - Ernst, S.; Haberhauer, G. (Chem.–Eur. J., 2009)

(untitled) - Haberhauer, G. (Angew. Chem., Int. Ed., 2008)
Angew. Chem., Int. Ed. 2008, 47, 3635–3638. doi:10.1002/anie.200800062

(untitled) - Kelly, T. R.; De Silva, H.; Silva, R. A. (Nature, 1999)

(untitled) - Hernández, J. V.; Kay, E. R.; Leigh, D. A. (Science, 2004)

(untitled) - Leigh, D. A.; Wong, J. K. Y.; Dehez, F.; Zerbetto, F. (Nature, 2003)

(untitled) - Vives, G.; Jacquot de Rouville, H.-P.; Carelle, A.; Launay, J.-P.; Rapenne, G. (Chem. Soc. Rev., 2009)

(untitled) - Darbost, U.; Penin, V.; Jeanneau, E.; Félix, C.; Vocanson, F.; Bucher, C.; Royal, G.; Bonnamour, I. (Chem. Commun., 2009)

(untitled) - McNitt, K. A.; Parimal, K.; Share, A. I.; Fahrenbach, A. C.; Witlicki, E. H.; Pink, M.; Bediako, D. K.; Plaisier, C. L.; Le, N.; Heeringa, L. P.; Vander Griend, D. A.; Flood, A. H. (J. Am. Chem. Soc., 2009)

(untitled) - Canary, J. W. (Chem. Soc. Rev., 2009)

(untitled) - Tanaka, K.; Kinbara, K. (Mol. BioSyst., 2008)

(untitled) - Kinbara, K.; Muraoka, T.; Aida, T. (Org. Biomol. Chem., 2008)

(untitled) - Muraoka, T.; Kinbara, K.; Aida, T. (Chem. Commun., 2007)

(untitled) - Muraoka, T.; Kinbara, K.; Aida, T. (Nature, 2006)

(untitled) - Muraoka, T.; Kinbara, K.; Kobayashi, Y.; Aida, T. (J. Am. Chem. Soc., 2003)

(untitled) - Zahn, S.; Canary, J. W. (J. Am. Chem. Soc., 2002)

(untitled) - Zahn, S.; Reckien, W.; Kirchner, B.; Staats, H.; Matthey, J.; Lützen, A. (Chem.–Eur. J., 2009)

(untitled) - Jeffery, J. C.; Rice, C. R.; Harding, L. P.; Baylies, C. J.; Riis-Johannessen, T. (Chem.–Eur. J., 2007)

(untitled) - Plitt, P.; Gross, D. E.; Lynch, V. M.; Sessler, J. L. (Chem.–Eur. J., 2007)

(untitled) - Sauvage, J. P. (Acc. Chem. Res., 1998)

(untitled) - Kelly, T. R.; Tellitu, I.; Sestelo, J. P. (Angew. Chem., Int. Ed. Engl., 1997)
Angew. Chem. 1997, 109, 1969–1972. doi:10.1002/ange.19971091727

(untitled) - König, B.; Hollnagel, H.; Ahrens, B.; Jones, P. G. (Angew. Chem., Int. Ed. Engl., 1995)
Angew. Chem. 1995, 107, 2763–2765. doi:10.1002/ange.19951072233

(untitled) - Lehn, J. M. (Angew. Chem., Int. Ed. Engl., 1990)
Angew. Chem. 1990, 102, 1347–1362. doi:10.1002/ange.19901021117

(untitled) - Rebek, J., Jr (Acc. Chem. Res., 1984)

(untitled) - Zhang, Z.; Bi, H.; Zhang, Y.; Yao, D.; Gao, H.; Fan, Y.; Zhang, H.; Wang, Y.; Wang, Y.; Chen, Z.; Ma, D. (Inorg. Chem., 2009)

(untitled) - Kim, N. G.; Shin, C. H.; Lee, M. H.; Do, Y. (J. Organomet. Chem., 2009)

(untitled) - Suresh, M.; Jose, D. A.; Das, A. (Org. Lett., 2007)

(untitled) - Rurack, K.; Radeglia, R. (Eur. J. Inorg. Chem., 2000)

(untitled) - LeGourriérec, D.; Kharlanov, V.; Brown, R. G.; Rettig, W. (J. Photochem. Photobiol., A: Chem., 1998)

(untitled) - Sitkowski, J.; Stefaniak, L.; Kaczmarek, L.; Webb, G. A. (J. Mol. Struct., 1996)

(untitled) - Kaczmarek, L.; Balicki, R.; Lipkowski, J.; Borowicz, P.; Grabowska, A. (J. Chem. Soc., Perkin Trans. 2, 1994)

Gaussian 03, Revision C.02 (Gaussian, Inc., 2004)